Chemical Characterization and In Vitro Gas Production Kinetics of Alternative Feed Resources for Small Ruminants in the Maltese Islands - Grazia Pastorelli; Kalliroi Simeonidis; Massimo Faustini; Angelo Le Mura; Mariagrazia Cavalleri; Valentina Serra; Everaldo Attard (Metabolites, 2023)
The ever-increasing human population, the problem associated with climate change and recent crises—COVID-19 disease and trade conflicts—all impacted on the availability and cost of animal feed raw materials. This is clearly visible in realities which heavily rely on importation such as islands and small states, where producers involved in the agricultural sector were strongly affected by the sharp increase in prices. To deal with these global issues, alternative resources are perceived to replace conventional ingredients. This work aimed at assessing the nutritive value of different resources (sheep feed, mature carob, Maltese bread, wild asparagus, prickly lettuce, and loquat) for small ruminants present in the Maltese Islands, analyzing their chemical composition, gas production kinetics and antioxidant properties. In general, the variation in chemical composition resulted in different rumen fermentation kinetics (p < 0.007). The ratio between GP-24 h and GP-48 h was higher in Maltese bread than other substrates; loquat, prickly lettuce and wild asparagus showed lower fermentation kinetics in accordance with their high NDF and ADF contents. The antioxidant activity may be partially related to the polyphenolic content that was higher in wild asparagus, prickly lettuce and loquat. All feed characteristic confirmed their potential to be included as ingredients in ruminant diets and as a source of fiber.